Kesiapan Belajar Anak TK dan SD Kelas 1 di Sekolah Bogor Raya Ditinjau dari Faktor Perkembangan Fisik dan Motorik, Kognitif, Bahasa dan Sosial Emosional [Readiness to Study of Kindergarten and Primary Grade 1 Level Students in Sekolah Bogor Raya Analyzed from Factors of Development of Physical and Motor, Cognitive, Language and Social Emotional] - Ria Nur Apriliyanti (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2022)
Early Childhood is an important period to introduce the children about the basic needs that can be used when they are adults. This period is special development stages. Human has individual development pattern as a result from several process such as biological process, cognitive process and social emotional process. Children development is more developing when they enter the school age. The problems occurred in the Early Childhood Education is children readiness to study. This research has a purpose to see the relationship physical and motor, cognitive, language and social emotional development that is considered as factors that could influence and support children readiness to study. This research conducted by giving questionnaire to 12 teachers of Kindergarten and Primary Grade 1 Level to see the development of 114 students in Sekolah Bogor Raya. Data gathered from questionnaire are processed using Excel and PSPP program. The result of this research shows that all independent variable (development of physical and motor, cognitive, language and social emotional) have a strong relation with the dependent variable (school readiness). Other result shows the development of physical and motor (44%), cognitive (59%), language (49%) and social emotional (44%) affected to students’ readiness to study. It is show that the development of cognitive and language are the most affected development towards Kindergarten and Grade 1 students’ readiness to study in Sekolah Bogor Raya.